Interweaving positive and critical perspectives in management learning and teaching. Issue 1 (February 2022) - Lavine, Marc; Carlsen, Arne; Spreitzer, Gretchen; Peterson, Tim; Roberts, Laura Morgan
Management learning is increasingly and rightfully called upon to address societal challenges beyond narrow concerns of economic performance. Within that agenda, we describe the generative aims of a special issue devoted to interweaving positive and critical perspectives in management learning and teaching. The five articles that comprise the issue describe the prospects for such interplay across a range of empirical and theoretical contexts. Together, these contributions suggest a way forward for work that is at once critical, positive, and reflexive. We identify key themes for future directions: the generative potential of contrarian learning dynamics, an ethics-first focus on ecological and human well-being, and the prospects of scholarly practice for systemic activism.